2013
DOI: 10.1002/bdrb.21055
|View full text |Cite
|
Sign up to set email alerts
|

Epoxiconazole‐Induced Degeneration in Rat Placenta and the Effects of Estradiol Supplementation

Abstract: Epoxiconazole (CAS-No. 133855-98-8) was recently shown to cause both a marked depletion of maternal estradiol blood levels and a significantly increased incidence of late fetal mortality when administered to pregnant rats throughout gestation (GD 7-18 or 21); estradiol supplementation prevented this epoxiconazole effect in rats (Stinchcombe et al., 2013), indicating that epoxiconazole-mediated estradiol depletion is a critical key event for induction of late fetal resorptions in rats. For further elucidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…In addition, hematologic parameters, clinical chemistry parameters, sex hormones, and the weights of previously identified target organs were determined in the dams at necropsy. The placentas were subjected to detailed histopathologic analysis (Rey Moreno et al, ). Finally, in an intervention experiment, groups of pregnant rats administered EPX from GD 7 to 21 were co‐treated with estrogen (i.e., ECP).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, hematologic parameters, clinical chemistry parameters, sex hormones, and the weights of previously identified target organs were determined in the dams at necropsy. The placentas were subjected to detailed histopathologic analysis (Rey Moreno et al, ). Finally, in an intervention experiment, groups of pregnant rats administered EPX from GD 7 to 21 were co‐treated with estrogen (i.e., ECP).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the incidence of vaginal hemorrhage was reduced with increasing ECP dose. It is possible that the vaginal hemorrhage was indicative of placental damage (Rey Moreno et al, ) and may have contributed to the observed anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the dose of 50 mg/kg body weight per day also elicited distinct maternal toxicity, as shown by reduced corrected body weight, reduced food consumption, clear anemia, and almost complete suppression of maternal serum estradiol. Placentas of fetuses undergoing late resorption showed degenerative changes of the labyrinth and trophospongium (Rey Moreno et al., ). These results indicate that intrauterine resorptions are not caused by a specific embryo‐fetotoxic effect of epoxiconazole, but rather due to a maternally mediated effect at toxic dose levels on the placentas, which are no longer able to adequately nourish the fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that intrauterine resorptions are not caused by a specific embryo‐fetotoxic effect of epoxiconazole, but rather due to a maternally mediated effect at toxic dose levels on the placentas, which are no longer able to adequately nourish the fetuses. Both the increased incidence of late resorptions and degeneration of the placentas could be prevented by maternal supplementation with estrogen (Rey Moreno et al., ; Stinchcombe et al., ). However, this supplementation did not prevent the other maternally toxic effects of epoxiconazole, that is, reduced body weight gain and anemia.…”
Section: Introductionmentioning
confidence: 99%